Prevalence of co-morbid conditions in Heart failure: an experience at tertiary care hospital - Dhungana, Sahadeb Prasad; Chaparia, Ankit; Sharma, Sanjib Kumar (Journal of Nobel Medical College, 2018)
Introduction: Patients with heart failure (HF) have various co-morbidities that complicate management and may adversely affect outcomes. HF guidelines provide little discussion on this topic and evidence is sparse. Material and Methods: This is a descriptive cross-sectional study on 240 consecutive patients with HF admitted from September 2016 to July 2017 at B.P. Koirala Institute of Health Sciences (BPKIHS), Nepal. All patients admitted with diagnosis of HF with reduced or preserved ejection fraction (NYHA functional class III/IV) based on Framingham Criteria and echocardiography assessments were included. Pre-defined co-morbid conditions were assessed. Results: Mean age of patients was 53.5 years and 53% were female. Most patients were in NYHA class III or IV (25% and 75% respectively) and 28.3% had ischemia as a cause of HF. Among co-morbidities, 85% of patients with HF had at least one co-morbidity. Anemia (68.3%), coronary artery disease (30.4%), hypertension (26.6%), diabetes (18.7%) and chronic kidney disease (7.5%) were the co-morbidities with the highest prevalence. Chronic obstructive pulmonary disease (3.7%), sleep apnea (2.5%), hypothyroidism (2.5%) and stroke (2.5%) were less common. Of all patients, only 15% had no co-morbidity, 40% had one co-morbidity, 22% had two co-morbidities, and 13 % had three or more co-morbidities. Conclusion: Co-morbidities are common problems and anemia is the most common in our scenario which could be of multi-factorial etiology. Careful attention to the diagnosis and management of specific co-morbidities may help to improve outcomes in patients with HF. Journal of Nobel Medical College Volume 6, Number 2, Issue 11 (July-December, 2017) Page:35-41